Krisis Kepemimpinan Kiai: Studi atas Kharisma Kiai dalam Masyarakat - Susanto, Edi (Program Pascasarjana UIN Sunan Ampel Surabaya, 2007)
In the hierarchy of a traditional society, Kiai is considered to belong to bothsocial and religious elite. He therefore holds an important role in his society. However,with the expansion of modernity that gives birth to a progressive and dynamic change inour society, Kiai is not regarded any more as the sole agent of social change. Hisfunction is becoming less and limited vis-Ã -vis modernity. The nature of his leadership isno longer religious, paternalistic and charismatic. Hence, Kiai should adapt himself tomodernity and change the style of his leadership to become more persuasive, participative,and rational if he is to survive.